Duchowni w korespondencji Wincentego Pola - Toruń, Włodzimierz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The above sketch The clergy in Wincenty Pol’s correspondence is devoted to Pol’s connections with the clergy of different Christian rites. The work was limited to only those examples that fund confimation in the epistolographie author of Mohort. The poet, know for his openness and ecumenical attitudes, kept in touch with the priests of other denominations. The warmth of youthful friendship, the fraternity of bloodhed together in the November Uprising, were the most durable bonds between Poles and patriotically disposed clergy. The poet’s connections with the clergy also determined common interests in the fields of scientific, literary, cultural, social and eccesial life.